Inheritance Rights of Children from Incestuous Marriages under Indonesia's Compilation of Islamic Law - Husni Ingratubun; Sri Iin Hartini; Huda Wahyudin (Universitas Cokroaminoto Yogyakarta, 2027)
Incest is a form of marriage that is expressly prohibited, both under Islamic law and Indonesian positive law. This prohibition does not automatically resolve the legal issues that arise when a child is born. This article aims to examine the legal status of children resulting from incestuous marriages in Indonesia and analyze their inheritance rights according to the Compilation of Islamic Law (Kompilasi Hukum Islam). This study uses a normative legal research method with statutory, conceptual, and case approaches, which legal material was analyzed qualitatively through descriptive-analytical techniques. The results indicate that incestuous marriage is a prohibited marriage and can be annulled based on Article 8 of Law Number 1 of 1974 as amended by Law Number 16 of 2019 and Articles 39 to 44 of the Compilation of Islamic Law, but the child born remains a legal subject protected by the state. Based on Article 100 of the Compilation of Islamic Law, the child's lineage is limited to the mother and her mother's family, so the child does not receive inheritance rights from his biological father through Islamic inheritance mechanisms, except through other legal instruments such as a gift, will, or mandatory will.